Perancangan Sistem Sensor dan Aktuator Nirkabel untuk Sistem SCADA Berbasis PLC - A. Agung Femin Himawan; Zulfajri Basri Hasanuddin; Faizal Arya Samman (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
In current PLC-based SCADA systems, sensor and actuator are generally connected to a PLC by wire. The wire however has many limitations, especially in term of flexibility. In the PLC-based SCADA system by wire, the number of the installed PLC will increase for each location that will be monitored and controlled. This research aims to design and implement a low cost, low power and reliable wireless sensor and actuator system, which can be used in the PLC-based SCADA system to overcome the limitations of wire media. The wirelesssensor and actuator system can also be used as an alternative to reduce the amount of the used PLC within the SCADA system. In this research, we have designed a wireless sensor and actuator system based on WPAN technology (IEEE 802.15.4), which is low cost, low power, and reliable. The results reveal that the wireless sensor and actuator system is able to operate well when they are implemented on the PLC-based SCADA system used to monitor and control the water filtration process in the tub filtration.